2014
DOI: 10.1111/aas.12302
|View full text |Cite
|
Sign up to set email alerts
|

Definition, prevalence, and outcome of feeding intolerance in intensive care: a systematic review and meta-analysis

Abstract: Clinicians and researchers frequently use the phrase 'feeding intolerance' (FI) as a descriptive term in enterally fed critically ill patients. We aimed to: (1) determine what is the most accepted definition of FI; (2) estimate the prevalence of FI; and (3) evaluate whether FI is associated with important outcomes. Systematic searches of peer-reviewed publications using PubMed, MEDLINE, and Web of Science were performed with studies reporting FI extracted. We identified 72 studies defining FI. In 33 studies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
239
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(248 citation statements)
references
References 52 publications
9
239
0
Order By: Relevance
“…Two studies defined feeding intolerance as the number of stools per 24 h period and/or the presence of vomiting or abdominal pain and/or tenderness [10,19]. Similarly, an adult systematic review of 72 intensive care studies [2] found that 43 different definitions of feeding intolerance were used, with GRV used in 88% of these alone or in combination with other signs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies defined feeding intolerance as the number of stools per 24 h period and/or the presence of vomiting or abdominal pain and/or tenderness [10,19]. Similarly, an adult systematic review of 72 intensive care studies [2] found that 43 different definitions of feeding intolerance were used, with GRV used in 88% of these alone or in combination with other signs.…”
Section: Resultsmentioning
confidence: 99%
“…The databases CINAHL plus, EBSCOhost, and Medline were searched in January 2018 using the term/s Bfeeding intolerance^and Btoleranceâ nd Bchild^or Bpediatric.^We also replicated the search strategy of the systematic review of feeding intolerance in adult intensive care [2]. Inclusion criteria were papers published in English or French and related to critically ill children (aged term to 17 years) without a limit applied to search years.…”
Section: Methodsmentioning
confidence: 99%
“…Observational data are consistent with the concept that GI dysfunction is clinically important, but the absence of an agreed definition of FI limits generalizability of research undertaken in this area [7]. The most frequently used definition of FI is as based on aspiration of the gastric residual volume (GRV) during enteral feeding, but the threshold volume chosen varies considerably between studies and investigators [8]. Other investigators have focused on the inability to reach a threshold amount of energy that is administered to a patient [9,10].…”
Section: Introductionmentioning
confidence: 90%
“…13 Feeding intolerance was primarily based on large gastric residual volumes (GRVs) together with other gastrointestinal symptoms. Disease severity has an impact on GRVs.…”
Section: Assess For Gastrointestinal Intolerance To Tube Feedingsmentioning
confidence: 99%